2022
DOI: 10.3390/foods11111602
|View full text |Cite
|
Sign up to set email alerts
|

Production of Innovative Essential Oil-Based Emulsion Coatings for Fungal Growth Control on Postharvest Fruits

Abstract: This work assessed the antimicrobial potential of natural essential oils (EOs) from cinnamon (CEO), zataria (ZEO), and satureja (SEO), applied natively or as coatings against Penicillium expansum and Botrytis cinerea during both in vitro and in vivo (on apple fruits) experiments. The induced inhibitory effect towards fungal growth, as a function of both EO type and concentration (75–1200 μL/L), was preliminarily investigated to select the most suitable EO for producing bacterial cellulose nanocrystals (BCNCs)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Undamaged fruits of similar size were transferred to the laboratory and kept at a temperature of 4 ± 1 • C until being tested. All the chemicals used in this research for the preparation of the coating and for conducting quality chemical tests were similar to those reported in our previous research works [11,[38][39][40]48]. The study utilized several commercially available materials.…”
Section: Raw Materials and Chemicalsmentioning
confidence: 99%
“…Undamaged fruits of similar size were transferred to the laboratory and kept at a temperature of 4 ± 1 • C until being tested. All the chemicals used in this research for the preparation of the coating and for conducting quality chemical tests were similar to those reported in our previous research works [11,[38][39][40]48]. The study utilized several commercially available materials.…”
Section: Raw Materials and Chemicalsmentioning
confidence: 99%
“…In this regard, it was shown that the incorporation of essential oils (EOs) in gelatin films had a positive effect on the water vapor barrier properties [2,[12][13][14][15][16], besides having well-known antimicrobial activity. For example, the use of cinnamon essential oil (CEO) for the generation of active packaging films and coatings for fungal growth control on postharvest fruits has recently been proposed [17]. Similarly, cellulose nanocrystals (CNCs) can be successfully used in combination with fish gelatin to yield nanocomposite structures with superior mechanical characteristics [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated different systems to obtain natural preparations based on EOs with antifungal potential in order to select the most suitable EO, carrier, and/or emulsifier for preparing the emulsion. Bacterial cellulose nanocrystals (BCNCs)/fish gelatin (GelA)-based emulsion [ 12 ], chitosan coatings and films loaded with different EOs [ 13 , 14 ], EOs encapsulated in lecithin [ 15 , 16 ], low-density polyethylene [ 17 ], octenyl succinic acid starch [ 18 ], Tween [ 19 ], zeolite, gelatin [ 20 ], and nanocellulose [ 21 ] have been tested. Significant results have been obtained by incorporating EOs into different coarse emulsions (CEs), nanoemulsion (NE), and Pickering emulsion (PE) at different concentrations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%